What is global history? - Conrad, Sebastian (Princeton, New Jersey Princeton University Press, 2016)
What is Global History? provides a comprehensive overview of this exciting new approach to history. The book addresses some of the biggest questions the discipline will face in the twenty-first century: How does global history differ from other interpretations of world history? How do we write a global history that is not Eurocentric yet does not fall into the trap of creating new centrisms? How can historians compare different societies and establish compatibility across space? What are the politics of global history? This in-depth and accessible book also explores the limits of the new paradigm and even its dangers, the question of whom global history should be written for, and much more.
Keywords: World history; History -- Philosophy; History -- Methodology; Globalization